Decreased microRNA-452 expression and its prognostic significance in human osteosarcoma. Issue 1 (December 2016) - Li, Ren-zeng; Wang, Li-min
Abstract Background MicroRNA-452 (miR-452) was previously reported to be dysregulated in several types of human cancers and involved in tumor progression. The aim of this study was to investigate the clinical significance and prognostic value of miR-452 expression in human osteosarcoma. Methods The expression of miR-452 was detected in 95 pairs of osteosarcoma specimens and adjacent noncancerous bone tissues using quantitative RT-PCR (qRT-PCR) assay. Then, the association of miR-452 levels with clinicopathological features and prognosis was analyzed. The roles of miR-452 in regulating osteosarcoma cell proliferation, apoptosis, and invasion were evaluated in vitro. Results miR-452 expression was significantly downregulated in osteosarcoma tissues than those in corresponding noncancerous bone tissues (P  < 0.001). Decreased miR-452 expression was linked to larger tumor size, high tumor grade, advanced clinical stage, distant metastasis, and shorter overall survival. Multivariate Cox regression analysis confirmed that low level of miR-452 expression predicted poor prognosis independently. miR-452 overexpression in MG-63 cells suppressed cell proliferation, promoted cell apoptosis, inhibited cell invasion, and led to decreased BMI1 protein levels. Conclusions These findings suggest that miR-452 downregulation may be involved in osteosarcoma formation and progression and that miR-452 would serve as a novel prognostic biomarker for patients with this disease.